Nutrition in Diabetic Nephropathy - Salwa, Agata Anna (Journal of Education, Health and Sport, 2018)
Introduction and purpose of the work. Diabetic kidney disease usually occurs at a late stage of diabetes and is often the result of long-term disease failure. As in diabetes alone, the diet used by the patient has a significant influence on how quickly the nephropathy will proceed. The aim of the study is to present issues related to dietary management in kidney diseases being complication of diabetes. . Brief description of the state of knowledge. People with type 2 diabetes usually struggle with overweight or obesity and hypertension. Obesity is one of the factors that causes the progression of diabetic kidney disease. A diet for such people requires a negative energy balance. Insulin itself increases appetite and the frequent occurrence of hypoglycaemia is the reason for increasing the number of meals. Summary. Diet is a very important element in the treatment of diabetes. It determines the maintenance of proper blood glucose and lipid (lipid) levels and optimal blood pressure values. A well-chosen diet reduces the risk of diabetic complications, as well as reduces the risk of vascular diseases. The right model of nutrition also plays an important role in the prevention and treatment of chronic diabetes complications.